2001
DOI: 10.3354/meps210093
|View full text |Cite
|
Sign up to set email alerts
|

Ciliate-generated advective seawater transport supplies chemoautotrophic ectosymbionts

Abstract: Oxygen concentration at the proximal part of Vorticella sp. did not increase during contraction, whereas during slow extension deoxygenated seawater was transported upwards and rapidly mixed with the surrounding oxygenated seawater when the ciliate started to beat its cilia. In both species rapid stalk contraction and subsequent slow extension enhanced the mixing of oxygenated and deoxygenated, H 2 S-containing seawater; the feeding currents (toroidal vortices) drew the surrounding seawater within reach of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…Here, the upward transport of seawater is caused by the unfolding and lifting of the bunched zooids, as illustrated in Fig. 4A-2 (Vopel et al 2001). These measurements revealed that sulphidic bottom water around the proximal region of Z. niveum colonies was displaced by oxygenated seawater from above after stalk contraction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the upward transport of seawater is caused by the unfolding and lifting of the bunched zooids, as illustrated in Fig. 4A-2 (Vopel et al 2001). These measurements revealed that sulphidic bottom water around the proximal region of Z. niveum colonies was displaced by oxygenated seawater from above after stalk contraction.…”
Section: Discussionmentioning
confidence: 99%
“…It was argued that rapid contraction of the ciliates increased the Reynolds number and prevented O 2 -laden seawater from being dragged along, which otherwise would push the sulphidic bottom water away before contact with the bacteria. Subsequently, this model was tested by applying fast-responding amperometric O 2 and H 2 S microelectrodes to bacteria-ciliate associations reared in the laboratory on H 2 S-releasing substrates (Vopel et al 2001). These measurements indicated that it is not the bathing of the ectobiotic bacteria alternately in anoxic, H 2 S-containing and O 2 -saturated seawater, but the cilia-generated advective seawater transport that turns the zooids external surface into an attractive microhabitat for chemoautotrophic bacteria; it was suggested that, in both ciliate species, rapid stalk contraction and subsequent slow extension merely contributed to the mixing of oxygenated and deoxygenated H 2 S-containing seawater within the substrate-seawater boundary layer.…”
Section: Introductionmentioning
confidence: 99%
“…According to observations on the vertical distribution of Caribbean Stilbonematinae (Laxus oneistus; Ott et al 1995) in laboratory experiments, these nematodes expose their symbionts alternately to reducing or oxidizing conditions by migrations through the chemocline in both directions (Ott et al 1991). Another strategy for providing sulfide oxidizing ectosymbionts with suitable environmental conditions has been suggested by Ott et al (1998) and modified by Vopel et al (2001) for a sedentary, feather-shaped, colonial peritrich ciliate that expands into oxygenated water and contracts into sulfidic water close to the substrate. The substrate is mangrove peat above which steep redox variations are present in the mm-range.…”
Section: Ecologymentioning
confidence: 99%
“…Ott et al (1998) proposed that Z. niveum supplies the bacterial symbionts with sulWde through periodic contraction into the anoxic and sulWdic diVusive boundary layer (DBL). Studies of the physical and chemical microenvironment around the colonies (Vopel et al 2001(Vopel et al , 2002(Vopel et al , 2005 could not conWrm this mechanism, but suggested that the feeding currents intercept sulWde and brings it to the symbiotic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…A trophic character of the symbiosis is suggested from observation of bacteria morphotypes in the food vacuoles (Bauer-Nebelsick et al 1996b), and by poor growth of the ciliates without ectosymbionts (Ott et al 1998;Vopel et al 2001). Ott et al (1998) proposed that Z. niveum supplies the bacterial symbionts with sulWde through periodic contraction into the anoxic and sulWdic diVusive boundary layer (DBL).…”
Section: Introductionmentioning
confidence: 99%